2021
DOI: 10.1371/journal.pmed.1003524
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of natural and synthetic cannabinoids in adults aged over 50 years: A systematic review and meta-analysis

Abstract: Background Cannabinoid-based medicines (CBMs) are being used widely in the elderly. However, their safety and tolerability in older adults remains unclear. We aimed to conduct a systematic review and meta-analysis of safety and tolerability of CBMs in adults of age ≥50 years. Methods and findings A systematic search was performed using MEDLINE, PubMed, EMBASE, CINAHL PsychInfo, Cochrane Library, and ClinicalTrials.gov (1 January 1990 to 3 October 2020). Randomised clinical trials (RCTs) of CBMs in those with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 100 publications
1
18
0
Order By: Relevance
“…No serious AEs were reported, and non-serious AEs were experienced in less than 12% of the cohort. The most common AEs observed (dizziness, nausea, dry mouth, and tinnitus) were similar with the results of a longitudinal study in older adults that observed the following most common AEs: dizziness, sleepiness/fatigue, dry mouth, and psychoactive sensation (Abuhasira et al 2018;Velayudhan et al 2021). Moreover, these AEs were similarly observed in the general population (Wang et al 2008).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…No serious AEs were reported, and non-serious AEs were experienced in less than 12% of the cohort. The most common AEs observed (dizziness, nausea, dry mouth, and tinnitus) were similar with the results of a longitudinal study in older adults that observed the following most common AEs: dizziness, sleepiness/fatigue, dry mouth, and psychoactive sensation (Abuhasira et al 2018;Velayudhan et al 2021). Moreover, these AEs were similarly observed in the general population (Wang et al 2008).…”
Section: Discussionsupporting
confidence: 85%
“…Cross-sectional surveys suggest older adults generally used cannabis for pain and sleep disorders, use had a positive impact on their lives, and they were less likely to report problematic cannabis use than younger adults (Brown et al 2020;Haug et al 2017;Reynolds et al 2018;Yang et al 2021). Moreover, Page 2 of 10 MacNair et al Journal of Cannabis Research (2022) 4:50 a systematic review and meta-analysis of cannabinoidbased medicines in older adults (≥ 50 years of age) concluded that they were safe and acceptable in this population (Velayudhan et al 2021). However, only one longitudinal study has examined the safety and effectiveness of medical cannabis in this population, where patients over 65 years of age at a medical cannabis clinic in Israel were followed for 6 months and pain intensity, quality of life, and adverse events (AEs) were monitored (Abuhasira et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The median of the mean age among eligible randomised trials we reviewed was 53; a separate review has concluded that, in general, cannabinoid based medicines are safe and acceptable in older adults. 78 Patients recruited among eligible trials were adults. However, the panel (which included a general paediatrician and a paediatric anaesthesiologist) could see no reason why the expected benefits would be systematically different among adolescents and emerging adults.…”
Section: Who Does It Apply To?mentioning
confidence: 99%
“…Cannabis has also been used for mental health conditions such as anxiety, depressive symptoms, insomnia, and post-traumatic stress disorder [ 14 , 27 ]. Among older adults, adverse events, which include dizziness, dry mouth, somnolence, and falls, are of concern [ 28 , 29 ] and may be more related to tetrahydrocannabinol (THC) than cannabidiol (CBD) [ 28 ]. Other concerns surrounding cannabis use among older adults include the presence of one or more medical ailments, use of multiple medications, and altered metabolic processing of drugs [ 30 ].…”
Section: Introductionmentioning
confidence: 99%